Metabolomic analysis of swainsonine poisoning in renal tubular epithelial cells - Zhang, Shuhang; Zhang, Yingqingqing; Yin, Hai; Liu, Yiling; Tang, Lihui; Zhu, Yanli; Sun, Pinzhi; Wu, Kexin; Zhao, Baoyu; Lu, Hao (Frontiers in Veterinary Science, 2024)
Locoweed is a poisonous plant widely present in grasslands around the world. Swainsonine, an indole alkaloid that, is the main toxic component of the locoweed. To understand the mechanism of SW -induced toxicity and to delineate the metabolic profile of locoweed poisoning we performed the LC-MS/MS untargeted metabolomic study to analyze metabolites in SW -treated renal tubular epithelial cells (0.8 mg/mL, 12 h) and in order to identify the SW -induced metabolomic changes. The analysis identified 2,563 metabolites in positive ion mode and 1,990 metabolites in negative ion mode. Our results showed that the metabolites were mainly benzenoids, lipids and lipid-like molecules, nucleosides, nucleotides, and analogues, organic acids and derivatives. The differential metabolites were primarily enriched in pathways involving bile secretion, primary bile acid biosynthesis, riboflavin metabolism, ferroptosis, drug metabolism-cytochrome P450, and primidine metabolism. We have screened out substances such as Swainsonine, 3alpha,7alpha-Dihydroxy-5betacholestanate, 2-Hydroxyiminostilbene, and Glycochenodeoxycholate, which may have the potential to serve as biomarkers for swainsonine poisoning. This study provides insights into the types of metabolomic alteration in renal tubular epithelial cells induced by swainsonine.